Technology Integration in Teaching: Applying TPACK Model for Vietnamese Universities - Thi Thanh Hai, Pham; Giang, Nguyen Thi Huong; Huyen, Nguyen Thi; Hanh, Pham Hong; Duong, Truong Ngoc (VNU Journal of Science: Education Research; Vol 40 No 3, 2024)
This research aims to synthesize international experiences in applying technology in teaching according to the TPACK model (Technological Pedagogical Content Knowledge), in order to draw lessons and apply them to Vietnamese universities. This article uses a theoretical research method, mainly synthesizing and analyzing texts from research papers published in large databases including Science Direct, Scopus, and Google Scholar, using keywords such as "TPACK" and "application of technology in teaching". To effectively apply technology, educational technologists have developed modern teaching frameworks, including the TPACK model, which combines three elements: (i) Technological knowledge; (ii) Pedagogical knowledge; and (iii) Content knowledge. Teachers need to harmoniously integrate these three elements when applying the TPACK model. In Vietnam, there have been some recent studies on the TPACK model in universities; however, the number of studies is still limited. This research aims to synthesize and analyze relevant studies on the application of technology in teaching according to the TPACK model. International experiences serve as practical lessons for Vietnamese universities to adapt and apply appropriately to the TPACK model, integrating technology with content and pedagogical methods in teaching to meet current practical requirements.